Norman Fairclough's Critical Discourse Analysis of the Representation of Adolescent Sexual Violence Cases in Online Media - Dini Windarini Windarini; Agus Hamdani Hamdani (Jurnal Bahasa Indonesia Prima (BIP), 2025)
This study aims to analyze the discourse representation of the rape case of a female teenager by four men in Bekasi reported by three online media, namely Detik.com, Kompas.com, and Metronews.com. The analysis focuses on Norman Fairclough's critical discourse analysis model, which includes three dimensions: microstructure, mesostructure, and macrostructure. This research method is descriptive qualitative, with documentation as the primary data collection technique. The microstructure analysis showed that the media used confident diction choices and syntactic structures to build the image of the perpetrators and victims, such as the use of the words "smoked alcohol" and "raped in turns," which caused specific emotional effects. Microstructural analysis shows the influence of media institutional background, editorial objectives, and the writing style of each media on the form of news presentation. Meanwhile, macrostructural analysis reveals that the news cannot be separated from the influence of patriarchal culture, the legal system, and social values that develop in society. All three show that the mass media convey information and shape an event's social construction by carrying specific ideological interests.